Pedicle Morphology Analysis in Adolescents with Lenke Type 5 Idiopathic Scoliosis in Thai Population - Pluemvitayaporn, Tinnakorn; Kaewmano, Tassana; Kunakornsawat, Sombat; Surapuchong, Suttinont; Ratanakoosakul, Warot; Tiracharnvut, Kitjapat; Pruttikul, Pritsanai; Piyasakulkaew, Chaiwat; Kittithamvongs, Piyabuth (Asian Journal of Neurosurgery, 2024)
Background The surgical management of adolescent idiopathic scoliosis (AIS) often incorporates the utilization of pedicle screws, which are three-column construct devices. A comprehensive understanding of the pedicle morphology is essential for determining the appropriate pedicle screw diameter. While previous studies have examined pedicle morphology in Lenke type 1 AIS, there is a scarcity of information about the pedicle morphology in Lenke type 5 AIS, especially in the Thai population.Objective The aim of this study is to analyze the morphology of the thoracolumbar pedicle, specifically the pedicle width and trajectory length on both the concave and convex sides within a sample of the Thai population diagnosed with Lenke type 5 AIS.Materials and Methods In this study, we used computed tomography (CT) measurements to examine the thoracolumbar pedicle morphology in Lenke type 5 AIS patients in the Thai population. We also analyzed the pedicle width and trajectory length on both concave and convex sides in 112 AIS patients with Lenke type 5 curvature.Results A total of 3,808 pedicles from 112 consecutive AIS patients of Lenke type 5 were enrolled in the study. It was observed that the transverse pedicle width was notably smaller on the concave side compared with the convex side in the apical region of the thoracolumbar spine (T12 to L2). Additionally, the pedicle width of T3 was also found to be significantly smaller on the concave side. Moreover, it was noted that the pedicle trajectory length is significantly longer on the concave side, indicating that the concave side in the apical region may have the capacity to accommodate a slightly longer pedicle screw at T3, T6, L2, L3, and L4.Conclusion Our analysis of measurements indicates that the thoracolumbar pedicle morphology in Lenke type 5 AIS among the Thai population typically shows smaller widths and longer trajectory lengths on the concave side. This information enhances our understanding of the appropriate selection of pedicle screw diameter and length for treating Lenke type 5 AIS in the Thai population.
Keywords: pedicle; pedicle morphology; adolescent idiopathic scoliosis; Lenke type 5